Sub-inverse and g-inverse of an Intuitionistic Fuzzy Matrix using Bi-implication Operator (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, we introduce a bi-implication operator for intuitionistic fuzzy matrix and discuss several properties. Further, we obtain sub-inverses and g-inverses of an intuitionistic fuzzy matrix using bi-implication operator.